2016
DOI: 10.2527/jas.2016-0820
|View full text |Cite
|
Sign up to set email alerts
|

Using single-step genomic best linear unbiased predictor to enhance the mitigation of seasonal losses due to heat stress in pigs

Abstract: The purposes of this study were to analyze the impact of seasonal losses due to heat stress in pigs from different breeds raised in different environments and to evaluate the accuracy improvement from adding genomic information to genetic evaluations. Data were available for 2 different swine populations: purebred Duroc animals raised in Texas and North Carolina and commercial crosses of Duroc and F females (Landrace × Large White) raised in Missouri and North Carolina; pedigrees provided links for animals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 19 publications
7
34
0
Order By: Relevance
“…These results are in partial agreement with Lewis and Bunter ( 2011 ), who did not observe relevant differences in heritability estimates on TNB, NBA and ABW expressed under different year seasons. As for the higher heritability in comfortable conditions, Silva et al ( 2014 ) reported higher heritability estimates for TNB in contemporary groups with better performance and Fragomeni et al ( 2016b ) found a similar trend when assessing HT based on body weight of purebred Duroc individuals.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results are in partial agreement with Lewis and Bunter ( 2011 ), who did not observe relevant differences in heritability estimates on TNB, NBA and ABW expressed under different year seasons. As for the higher heritability in comfortable conditions, Silva et al ( 2014 ) reported higher heritability estimates for TNB in contemporary groups with better performance and Fragomeni et al ( 2016b ) found a similar trend when assessing HT based on body weight of purebred Duroc individuals.…”
Section: Discussionmentioning
confidence: 92%
“…In general, genetic analysis of HT in growing/finishing pigs are based on a heat-load function for live or carcass weight (Zumbach et al, 2008a , b ; Fragomeni et al, 2016a ). HT based on growth traits is moderately heritable (Fragomeni et al, 2016a , b ), but there is a gap in knowledge on the genetic mechanisms of HS response in sows since only differences between maternal genetic lines have been reported (Peltoniemi et al, 1999 ; Bloemhof et al, 2008 ). Furthermore, the genetic correlations among reproductive traits expressed in different seasons of the year are lower than unity (Lewis and Bunter, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a common practice, variance components obtained based only on phenotypes and pedigree were used to compute both BLUP and ssGBLUP (Fragomeni et al, 2016;Oliveira et al, 2019). Accuracies of breeding values for traditional and genomic evaluations for single-boar semen and pooled semen considering unknown and known boar information are in Tables 2 and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Reproductive techniques such as artificial insemination have allowed elite animals to transmit their genetic merit in various environments, which could lead to the phenomenon of G × E interactions. Previous reports have shown the existence of G × E interactions in pigs (Fragomeni et al., 2016; Knap & Su, 2008; Silva et al., 2014).…”
Section: Introductionmentioning
confidence: 91%